Outcome after osteochondroplasty and relative neck lengthening for patients with healed Legg-Calvé-Perthes disease: a retrospective cohort study of patients with hip-deformities treated with osteochondroplasty and relative neck lengthening. Issue 3 (May 2021) - Risto, Olof; Sandquist, Sofia; Lind, Stefan; Madan, Sanjeev
Aims: Our main objectives were to evaluate the effect of surgery using self-assessed health scores. Secondary objectives were to correlate outcome with grade of deformity (Stulberg classification I–V) or age at surgery and whether additional periacetabular osteotomy (PAO) is beneficial for patients with concurrent acetabular dysplasia. Methods: This was a retrospective cohort and in part a cross sectional study using a planned clinical and radiological follow-up of patients. All patients with healed Legg-Calvé-Perthes disease (LCPD) treated with osteochondroplasty and relative neck lengthening using surgical hip dislocation, with or without periacetabular osteotomy (PAO) were included. A total of 39 patients were identified and invited to participate (29 males and 10 females) of which 32 accepted. Radiographic assessment and Stulberg classification were obtained. The Nonarthritic Hip Score (NAHS), modified Harris Hip Score (mHHS) and the VAS scale of EQ-5D-5L were used. Results: The majority of the patients experienced improvement (74%, n =  27) and 21 patients (78%, n =  27) found the surgery worthwhile. Preoperative Stulberg II and III patients (83% improvement) showed better results than Stulberg IV and V patients (56% improvement) ( n =  27, p =  0.121). There was significantly better patient-satisfaction for those younger than 29 years of age (⩽18 years old (92%), 19–28 years old (89%), ⩾29 years old (67%), x 2 (2) = 8512, n =  27, p =  0.022) and a negative correlation for age at onset of LCPD and mHHS ( r  = –0.420, p =  0.046, n =  23). Patients with concurrent acetabular dysplasia ( n =  19), 82% (9 of 11) improved after additional PAO compared to 63% (5 of 8) who were not operated on with PAO. Conclusion: This procedure is worthwhile in selected cases except for severe deformity (Stulberg IV and V) and patients >28 years of age.